Characterization and recovery of mercury from spent fluorescent lamps - Jang, Min; Hong, S.M.; Park, J.K. (Elsevier, 2005)
Fluorescent lamps rely on mercury as the source of ultraviolet radiation for the production of visible light. Partitioning of mercury among vapor phase, loose phosphor powders produced during breaking and washing steps, glass matrices, phosphor powders attached on the glass and aluminum end caps was examined from simulated laboratory lamp recycling tests for different types of spent and new fluorescent lamps. Mercury concentrations in lamp glasses taken from commercial lamp recyclers were also analyzed for comparison with the simulated results of spent and new lamps of different types. The mercury content of the glass from spent lamps was highly variable depending on the lamp type and manufacturer; the median values of the mercury concentration in glasses for spent 26- (T8) and 38-mm (T12) diameter fluorescent lamps were approximately 30 and 45 Î¼g/g, respectively. The average mercury concentration of samples taken from recycler A was 29.6 Î¼g/g, which was about 64 of median value measured from the spent T12 lamps. Over 94 of total mercury in lamps remained either as a component of phosphor powders attached inside the lamp or in glass matrices. New T12 lamps had a higher partitioning percentage of elemental mercury in the vapor phase (0.17) than spent T12 lamps (0.04), while spent lamps had higher partitioning percentages of mercury resided on end-caps and phosphor powders detached from the breaking and washing steps. The TCLP values of simulated all lamp-glasses and samples obtained from recyclers were higher than the limit of LDR standard (0.025 mg/L). After investigating acid treatment and high temperature treatment as mercury reclamation techniques, it was found that heating provided the most effective mercury capture. Although the initial mercury concentrations of individual sample were different, the mercury concentrations after 1 h exposure at 100Â°C were below 4 Î¼g/g for all samples (i.e., <1 remaining). Therefore, it is recommended that heating be used for recovering mercury from spent fluorescent lamps. Â© 2004 Elsevier Ltd. All rights reserved.